THE IMPACT OF THERMAL PERFORMANCE ON THE ROOF SURFACE TO ENERGY EFFICIENT OF HIGH-RISE BUILDING IN THE TROPICAL REGION - Sri Yuliani; Wiwik Setyaningsih (ARSITEKTURA, 2018)
The surface temperature of the building material may release a heat load in the micro-environment. The largest building envelope receives the heat load of solar radiation is the roof. The strategic roof position at the top of the building has the opportunity to radiate heat received into the environment. Heat emissions lead to rising temperatures, so it is necessary to lower the temperature in micro-environment. When the heat of the building is not lowered will lead to an increase in the urban heat island (UHI). The objective of the study was to find the relationship between the thermal performance of the roof of the building and the energy efficiency in the high-rise building, in order to establish efficient thermal comfort. The research method uses experimental way in real model which is in Surakarta City, as humid tropical climate area. The result of the study is a comparison of the heat performance of three roofing materials which would later recommend the criteria of energy efficient roof for high buildings.